Maudite Soit La Guerre - Machin, Alfred (Belgium : Netherlands Filmmuseum, 1914)
Released just months before the outbreak of World War I, Machin’s pacifist masterpiece is often celebrated for its prescient and realistic depiction of aerial combat, with dogfights so startling that the film was perceived, during its original release, as belonging to the fantasy genre. A classic Romeo-and-Juliet tale of lovers divided by the outbreak of war between their homelands. French intertitles, simultaneous English translation.
Keywords: Fiction films